2003
DOI: 10.1017/s0967199403002144
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prooxidant agents added at the morula/blastocyst stage on bovine embryo development, cell death and glutathione content

Abstract: Two prooxidant agents, 2,2′-azobis(2-amidinopropane)dihydrochloride (AAPH), a generator of free radicals in the culture medium, and buthionine sulfoximine (BSO), an inhibitor of glutathione synthesis, were used to reinforce from the morula stage (day 5 post-insemination, p.i.) the oxidative stress encountered by bovine embryos in culture. Exposure to increasing concentrations of both prooxidants from the morula stage did not affect blastocyst formation but some blastocysts were found degenerated on day 8 in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 54 publications
(101 reference statements)
3
16
0
Order By: Relevance
“…Both pro-oxidants, AAPH and BSO, induced the degeneration of some blastocysts, as previously described (Feugang et al, 2003). The timing of appearance of the first signs of degeneration was not different between the two prooxidants (Table 2).…”
Section: Experiments 1: Kinetics Of Embryo Degeneration and Characterisupporting
confidence: 74%
See 2 more Smart Citations
“…Both pro-oxidants, AAPH and BSO, induced the degeneration of some blastocysts, as previously described (Feugang et al, 2003). The timing of appearance of the first signs of degeneration was not different between the two prooxidants (Table 2).…”
Section: Experiments 1: Kinetics Of Embryo Degeneration and Characterisupporting
confidence: 74%
“…Total cell number and the proportion of apoptotic nuclei detected by the TUNEL technique were not different between blastocysts resisting to oxidative stress at day 8 and control blastocysts of the same age. Moreover, we previously showed that hatching rates were not affected (Feugang et al, 2003). The quality of resisting embryos using those limited criteria seems unaffected by the treatment.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In NT embryos, the percentage of embryos with DNAfragmented nuclei is apparently higher than in in vitro fertilization (IVF) embryos for cows (Fahrudin et al, 2002;Feugang et al, 2003) and pigs (Hao et al, 2003). During mouse embryonic development, multiple caspases and antiand pro-apoptotic genes are expressed (Cohen, 1997;Cryns and Yuan, 1999;Salveson and Dixit, 1997), and in cows, antiand pro-apoptotic genes such as Bcl2, Bcl-xL, and Bax are involved in regulation of apoptosis in preimplantation embryos (Augustin et al, 2003;Kolle et al, 2002;Lonergan et al, 2003;Yang et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The expression patterns of genes such as superoxide dismutase (SOD) enzymes, heat shock protein (hsp) and Bcl2/Bax are the results of high level of ROS in culture systems (Lequarre et al, 2001;Lonergan et al, 2003c). It has been reported that culture conditions associated with an increased level of prooxidants induce blastocyst degeneration only observed on Day 8 post-insemination (pi), whereas these blastocysts were morphologically acceptable for a transfer on Day 7 pi (Feugang et al, 2003;Feugang et al, 2004). This suggested that the low fetal development and high incidence of abnormalities (i.e., chromosomes aberrations) observed after embryo transfer are more likely due to a progressive accumulation of toxic effects during culture (Lonergan et al, 2004).…”
Section: Short-term Effectsmentioning
confidence: 99%